Federalism, nationalism and development : India and the Punjab economy - Singh, Pritam, 1949- (London ; New York : Routledge, 2008)
This book throws new light on the study of India's development through an exploration of the triangular relationship between federalism, nationalism and the development process. The book concentrates on the federal structure of the Indian polity and it examines the evolution of the relationship between the centre and the state of Punjah, taking into account the emergence of Punjabi Sikh nationalism and its conflict with Indian nationalism.
Includes bibliographical references (p. 195-213) and index.
rpm 29/04/13
Loans
Keywords: Central-local government relations -- India -- Punjab; Punjab (India) -- Economic conditions; Federal government -- India; Nationalism -- India